Predation by female chimpanzees: Toward an understanding of sex differences in meat acquisition in the last common ancestor of Pan and Homo. Issue 110 (September 2017) - Gilby, Ian C.; Machanda, Zarin P.; O'Malley, Robert C.; Murray, Carson M.; Lonsdorf, Elizabeth V.; Walker, Kara; Mjungu, Deus C.; Otali, Emily; Muller, Martin N.; Emery Thompson, Melissa; Pusey, Anne E.; Wrangham, Richard W.
Abstract: Among modern foraging societies, men hunt more than women, who mostly target relatively low-quality, reliable resources (i.e., plants). This difference has long been assumed to reflect human female reproductive constraints, particularly caring for and provisioning mates and offspring. Long-term studies of chimpanzees ( Pan troglodytes ) enable tests of hypotheses about the possible origins of human sex differences in hunting, prior to pair-bonding and regular provisioning. We studied two eastern chimpanzee communities (Kasekela, Mitumba) in Gombe, Tanzania and one (Kanyawara) in Kibale, Uganda. Relative to males, females had low hunting rates in all three communities, even where they encountered red colobus monkeys (the primary prey of chimpanzees) as often as males did. There was no evidence that clinging offspring hampered female hunting. Instead, consistent with the hypothesis that females should be more risk-averse than males, females at all three sites specialized in low-cost prey (terrestrial/sedentary prey at Gombe; black and white colobus monkeys at Kanyawara). Female dominance rank was positively correlated with red colobus hunting probability only at Kasekela, suggesting that those in good physical condition were less sensitive to the costs of possible failure. Finally, the potential for carcass appropriation by males deterred females at Kasekela (but not Kanyawara or Mitumba) from hunting in parties containing many adult males. Although chimpanzees are not direct analogs of the last common ancestor (LCA) of Pan and Homo, these results suggest that before the emergence of social obligations regarding sharing and provisioning, constraints on hunting by LCA females did not necessarily stem from maternal care. Instead, they suggest that a risk-averse foraging strategy and the potential for losing prey to males limited female predation on vertebrates. Sex differences in hunting behavior would likely have preceded the evolution of the sexual division of labor among modern humans.